Investigation of a High Karlovitz, High Pressure Premixed Jet Flame with Heat Losses by LES. Issue 11 (1st November 2020) - Gruhlke, P.; Janbazi, H.; Wlokas, I.; Beck, C.; Kempf, A. M.
ABSTRACT: Large-eddy simulations (LES) are presented for a lean preheated high pressure jet flame experiment for which detailed in situ data is available, using a finite rate chemistry (FRC) approach in a gas-turbine model combustor at high Karlovitz number. The impact of the different combustion models on the flame stabilization in the simulation is investigated and the predicted carbon monoxide (CO) and nitric oxide (NO x ) emissions are analyzed. For the FRC approach, the DRM19 reaction mechanism and a new inhouse skeletal mechanism are applied. The more detailed DRM19 mechanism is extended to include OH* species, the new skeletal mechanism includes CO and NO x reaction paths. An industry relevant tabulated chemistry approach is assessed on the ability to predict this lifted flame, where the flamelet tables are calculated from the detailed GRI-3.0 reaction mechanism. A dynamic thickened flame approach is applied to resolve the flame on the numerical grid including a model for the turbulence chemistry interaction. Adiabatic and non-adiabatic simulations are compared, where the impact of heat losses due to chamber cooling and thermal radiation are considered. Velocities, temperatures, fuel mass fractions and CO and NO x mass fractions at different axial locations are in good agreement to the experiments when heat losses are considered. The significant flame lift was correctly predicted by the FRC approach with DRM19 chemistry when non-adiabatic boundary conditions were applied. This provides evidence that the flame is stabilized by flame propagation assisted by auto ignition and that ignition-delay times of mixtures composed of fresh and burnt gases need to be captured by the applied models.